2012
DOI: 10.1021/jp211054u
|View full text |Cite
|
Sign up to set email alerts
|

Protein Dynamics in Organic Media at Varying Water Activity Studied by Molecular Dynamics Simulation

Abstract: In nonaqueous enzymology, control of enzyme hydration is commonly approached by fixing the thermodynamic water activity of the medium. In this work, we present a strategy for evaluating the water activity in molecular dynamics simulations of proteins in water/organic solvent mixtures. The method relies on determining the water content of the bulk phase and uses a combination of Kirkwood-Buff theory and free energy calculations to determine corresponding activity coefficients. We apply the method in a molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 93 publications
4
94
0
Order By: Relevance
“…The same question may be asked in the cases where water is replaced by organic solvents (Soares et al, 2003;Chen et al, 2008;Wedberg et al, 2012;Klibanov, 2010). Van der Waals interactions still operate, and dipolar interactions will increase in strength as water is removed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same question may be asked in the cases where water is replaced by organic solvents (Soares et al, 2003;Chen et al, 2008;Wedberg et al, 2012;Klibanov, 2010). Van der Waals interactions still operate, and dipolar interactions will increase in strength as water is removed.…”
Section: Discussionmentioning
confidence: 99%
“…An important family of experimental tools for studying proteins and protein-protein interactions consists of matrix-assisted laser desorption/ionization (MALDI), time-of-flight mass spectrometry (TOF) and electrospray (Smith et al, 1990;Robinson et al, 2007;Wyttenbach and Bowers, 2007;Breuker and McLafferty, 2008;Benesch and Robinson, 2009;Liu et al, 2009;Liu and Schey, 2008;Barrera et al, 2008). Many proteins, and many protein-protein complexes, retain their structural integrity in vacuo, at least for a sufficiently long time, for many of their essential structural features to be retained and be capable of study in intimate detail (Patriksson et al, 2007;Meyer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have explored different approaches to this property via MD simulation (Wedberg, Abildskov, and Peters 2012). Two main strategies to study how protein properties depend on water activity are termed "real-time" control and "a posteriori" analysis.…”
Section: Enzyme Solutionsmentioning
confidence: 99%
“…It has been reported that motions of surface residues are linked to the stability of lipase in polar solvents (methanol, acetonitrile, DMSO and dimethylformamide) [17], [42] and [43]. It is also known that polar solvents, as dehydrating agents, are able to bind to the surface residues of enzyme (lipase, protease and -12 -other enzymes), perturbing the essential layer of water that provides enzyme with conformational flexibility needed for catalysis and thus decreasing the enzymatic activity [40], [44], [45], [46], [47], [48], and [49]. Therefore, the capacity of lipases to tolerate polar solvents could be improved by introducing more intra-protein interactions on the flexible surface region or reducing the interactions between polar solvent molecules and enzyme surface residues.…”
Section: Computational Prediction Of a Stabilizing Mutation For Tllmentioning
confidence: 99%